INVESTMENT DECISION-MAKING AND EQUITY VALUATION IN PUBLICLY LISTED FOOD AND BEVERAGE COMPANIES - Rodríguez, Maria Gonzales; Anderson, Liam (Ayden International Journal of Banking, Finance and Technology, 2024)
This study examined the relationship between capital investment and stock valuation of quoted food and beverage manufacturing firms in Nigeria. Secondary data obtained from 22 quoted food and beverage manufacturing firms from 2012 - 2021 obtained from the Nigerian Stock Exchange Fact book and annual reports of the quoted food and beverage manufacturing firms. The study modeled stock valuation as the dependent variables while capital investment on equipment, capital investment on plants, human capital expenditure, sustaining capital expenditure, capital investment on expansion projects. Panel data methodology is employed while the fixed effects model is used as estimation technique at 5% level of significance. Fixed effects, random effects and pooled estimates were tested while the Hausman test was used to determine the best fit. The study found that the independent variables explained 86.2 percent variation in the dependent variable which is stock value, the beta coefficient indicates that found that sustainable capital investment reduced stock value by 0.01 percent, capital investment on expansion increased stock value by 0.005 percent, capital investment on plant reduced stock value by 4 percent, capital investment on human capital added 0.09 percent while capital investment on equipment added stock value by 0.007 percent within the time periods of the study. The study conclude that capital investment have significant effect on valuation of the quoted food and beverage manufacturing firms. We recommend that capital investment policy should be integrated into corporate financing policy of the quoted firms